(untitled) (Journal of the College of Basic Education, 2024)
The aim of this research is to explore the impact of the "redescription" strategy on acquiring physics concepts and central thinking among second-grade female students. The research population was selected from intermediate and high schools under the supervision of the Directorate of Education in Baghdad/Al-Rusafa for the academic Yea (2023-2024). The researcher intentionally chose a sample from Al-Tamouh Intermediate School for Girls, with a sample size of 60 students, divided into 30 students for the experimental group and 30 students for the control group. The researcher taught the experimental groupusing the Redescription strategy, while the control group was taught using traditional methods.The researcher identified the scientific material to be taught in the first five chapters of the physics textbook for the second-grade intermediate level. Additionally, the researcher prepared typical teaching plans for both research groups and conducted a test to assess the acquisition of physics concepts and central thinking. The research results were statistically analyzed using the t-test and other statistical methods. The results showed that the experimental group, taught using the redescription strategy, outperformed the control group, taught using traditional methods, in acquiring physics concepts and central thinking. Based on these findings, the researcher developed several recommendations and suggestions.